Estimation of an Optimal Chemotherapy Utilisation Rate for Upper Gastrointestinal Cancers: Setting an Evidence-Based Benchmark for the Best-Quality Cancer Care - Weng Ng; Susannah Jacob; Geoff Delaney; Viet Do; Michael Barton (Gastroenterology Research and Practice, 2015)
Aims. The proportion of patients with upper gastrointestinal cancers that received chemotherapy varies widely in Australia and internationally, indicating a need for a benchmark rate of chemotherapy utilisation. We developed evidence-based models for upper gastrointestinal cancers to estimate the optimal chemotherapy utilisation rates that can serve as useful benchmarks for measuring and improving the quality of care. Materials and Methods. Optimal chemotherapy utilisation models for cancers of the oesophagus, stomach, pancreas, gallbladder, and primary liver were constructed using indications for chemotherapy identified from evidence-based guidelines. Results. Based on the best available evidence, the optimal proportion of upper gastrointestinal cancers that should receive chemotherapy at least once during the course of the patients’ illness was estimated to be 79% for oesophageal cancer, 83% for gastric cancer, 35% for pancreatic cancer, 80% for gallbladder cancer, and 27% for primary liver cancer. Conclusions. The reported chemotherapy utilisation rates for upper gastrointestinal cancers (with the exception of primary liver cancer) appear to be substantially lower than the estimated optimal rates suggesting that chemotherapy may be underutilised. Further studies to elucidate the reasons for the potential underutilisation of chemotherapy in upper gastrointestinal tumours are required to bridge the gap between the ideal and actual practice identified.